Career Success of Managers and the Moderating Roles of Gender and Managerial Level in the Malaysian Public Sector - Mohd Rasdi, Roziah (2009)
Examination of the career literature indicated that career success studies did not consider the diverse effects of the individual, structural and behavioral approaches. In addition, there were less career success studies in testing the moderating role of gender and managerial level. Thus, this study aims to examine the factors explaining career success (objective and subjective) of managers and the moderating roles of gender and managerial level in the relationships between the career success variables. This crosssectional correlational study was conducted on 288 managers of various managerial grades who worked in several public organizations in Putrajaya, the federal administrative center of Malaysia, and managers who attended the training program conducted by the National Institute for Public Administration. They were chosen using a stratified random sampling procedure. A quantitative survey was designed using selfadministered questionnaire. Managers' career success was conceptualized using the Social Cognitive Career Theory (SCCT). The theory highlights the three main career success approaches and the reciprocal person-environment interactions, all of which explain individual's career success.